Nanosensors in the detection of antihypertension drugs, a golden step for medication adherence monitoring - Mobed, Ahmad; Gholami, Sarah; Tahavvori, Amir; Ghazi, Farhood; Masoumi, Zahra; Alipourfard, Iraj; Naderian, Ramtin; Mohammadzadeh, Mehran (Heliyon, 2023)
Hypertension is associated with structural and functional changes in blood vessels with increased arteriosclerosis, vascular inflammation, and endothelial dysfunction. Decreased adherence (compliance) to antihypertensive medications contributes significantly to morbidity and mortality in hypertensive patients. Antihypertensive drugs (AHTDs) and lifestyle changes are the main cornerstones for treating hypertension. Several approaches have been described in the literature for determining AHTDs based on different analytical techniques. Amongst biosensors are one of the most attractive tools due to their inherent advantages. Biosensors are used for the detection of wide range of biomarkers as well as different drugs in past two decades. The main focus of the present study is to review the latest biosensors developed for the detection of AHTDs. Readers of the present study will be able to familiarize themselves with biosensors as advanced and modern diagnostic tools while reviewing the most widely used AHTDs. In the present study, the routine methods are first reviewed and while examining their advantages and disadvantages, biosensors have been introduced as ideal alternative tools. [Display omitted]